2020
DOI: 10.14429/dlsj.5.15254
|View full text |Cite
|
Sign up to set email alerts
|

Protein Profile of Human Lung Epithelial Cells (A549) Revealing Deviation in Cytoskeleton Proteins in Response to Zinc Oxide Nanoparticles Exposure

Abstract: Zinc oxide nanoparticles (ZnO NPs) are widely used in biomedicine and scientific research because of their high dissolution property and bioavailability. On the contrary, this property also increases the intracellular reactivity, accessibility and cytotoxicity. These nano-bio interactions could induce undesirable changes in the proteome of the interacting cells, especially in the lung cells as these are the primary contact site. However, the potential effects of ZnO NPs exposure on proteome remain unclear. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The characterization of these NPs in the culture medium was performed through dynamic light scattering (DLS). The actual size and morphology of the particles were measured through transmission electron microscopy (TEM) (Anand et al, 2020; Jain et al, 2014). A microliter aliquot of NPs in Milli-Q water was added to a 300 mesh carbon-coated grid.…”
Section: Methodsmentioning
confidence: 99%
“…The characterization of these NPs in the culture medium was performed through dynamic light scattering (DLS). The actual size and morphology of the particles were measured through transmission electron microscopy (TEM) (Anand et al, 2020; Jain et al, 2014). A microliter aliquot of NPs in Milli-Q water was added to a 300 mesh carbon-coated grid.…”
Section: Methodsmentioning
confidence: 99%
“…They also suggested that HSP70 play an important role for cellular motility, migration, and invasion. Increased expression of HSP70 was also found in A549 cells to protect them from hypoxic injury and to response to zinc oxide nanoparticles exposure (141,142). The exposure of cigarette smoke has been reported as another cause for inducing the up-regulated expression of HSP70 in rat brain (143).…”
mentioning
confidence: 85%